Comparison of Percutaneous Internal Ring Suturing (PIRS) versus Open Ligation of the Patent Processus Vaginalis for the Treatment of Communicating Pediatric Hydrocele - Zenon Pogorelić; Petar Stanić; Marko Bašković (MDPI AG, 2024)
Background: Although the laparoscopic approach become standard for the treatment of many surgical conditions many studies still debating whether laparoscopic surgery has significant advantages over open surgery in regards to hernia or hydrocele treatment. This study aimed to evaluate the outcomes of treatment of treatment of communicating hydrocele in pediatric patients between laparoscopic percutaneous internal ring suturing (PIRS) and open ligation of the patent processus vaginalis (PPV). Methods: The medical records of pediatric patients who underwent surgery for communicating hydrocele between 1 January 2019 and 1 January 2024 were retrospectively reviewed. The primary objective of the study is to investigate the outcomes of treatment (complications and recurrence rates) of communicating hydrocele in children between laparoscopic and open surgical approaches. Secondary outcomes of the study are the duration of surgery and anesthesia, length of hospital stay (LOS), frequency of hospital readmissions (ReAd) and unplanned return to the operating room (uROR). Results: A total of 198 children underwent surgery for a communicating hydrocele (205 repairs, as 7 cases were bilateral) and were included in the study. Of these, 87 children underwent a PIRS, while the remaining 111 cases underwent open ligation of the PPV. No recurrence of the hydrocele was observed in any of the study groups. Intraoperative complication (epigastric vein injury) was noted in two cases in both groups (2.3% vs. 1.8%, p > 0.999). A slightly higher number of postoperative complications was observed in the open group (n = 7, 6.3%) compared to the PIRS group (n = 2, 2.3%) (p = 0.190). The median duration of surgery (15 min (IQR 10, 17) vs. 21 min (IQR 15, 25); p < 0.001) and anesthesia (30 min (IQR 25, 40) vs. 40 min (IQR 35, 40); p < 0.001) were significantly lower in the PIRS group compared to open ligation of the PPV. In addition, a significantly shorter median of LOS was observed in the PIRS group compared to the open PPV group (9 h (IQR 8, 12) vs. 24 h (IQR 12, 24; p < 0.001). No cases of ReAd and uROR were observed in any of the study groups. Conclusions: PIRS is a safe and effective laparoscopic technique that can be used in the treatment of communicating hydrocele in children. PIRS showed excellent outcomes and a low incidence of complications and recurrences, comparable to traditional open surgery.